ANALISIS STATIS UNTUK MODIFIKASI OUTER FRONT DOOR MOBIL ESEMKA RAJAWALI 2 - Sarwoko, Sri Wahyu (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2018)
ABSTRACT The objective of the research was to find out the engineering drawing outer front door of Esemka Rajawali 2 Car by using reverse engineering method. The devices used in this reverse engineering method were the manual of 3D coordinate measurement machine and digital camera, focused on outer front door component. The coordinate data of X, Y, and Z from the manual of 3D coordinate measurement machine and the data acquired from the digital camera in the form of pictures were analyzed with solidwok software was changed into engineering drawing and then its size was compared with the result of average size difference of 1,52 mm. The simple surface form of the Esemka Rajawali 2 Car outer front door can produce a little size difference. Static analysis was conducted on Esemka Rajawali 2 Car surface outer front door employing solidwok software by giving the weight of 950kg or 9500N. Meanwwhile, the material used was alloysteel with the thickness of 0,8mm in order to get the modification of outer front door with the smallest deformation. The result of Esemka Rajawali 2 Car outer front door’s modification was 3,32 mm in which it was way smaller compared with the deformation of the Esemka Rajawali 2 Car outer front door’s original design, that was 17,99 mm. Keywords: reverse engineering, engineering drawing, outer front door, surface, esemka car, manual of 3D coordinate measurement machine